Conductas alimentarias de riesgo, asociadas a la imagen corporal de los adolescentes del Colegio de Bachillerato 27 de Febrero. - Quizhpe Benítez, María Gricela (2018)
The disorders caused by risk eating behaviors are anorexia nervosa characterized by an intense fear of weight gain and bulimia nervosa that is expressed by recurrent episodes of voracity followed by purging behaviors. These disorders mainly affect people between 10 and 24 years, constituting the most prevalent chronic diseases in adolescents and turning them into the mental health disorders with higher mortality worldwide. The current qualitative and quantitative, descriptive and cross-sectional study was carried out in teenagers of the "27 de Febrero" High-school, whose objectives corresponded to identify risky eating behaviors and the aspects that influence self-perception; a survey was applied to 205 students, the same that contained two questionnaires "Food Attitudes" and "Body Form". The corresponding results indicate that adolescents of the male sex show risky eating behavior in a lower percentage; women showed risky eating behaviors such as 76.6% diets and 74.8% worry about food; and, the aspect that influences the body image of adolescents is the body dissatisfaction that affects 65.3% of men and 82.2% of women. The female sex is the one that presents risky eating behaviors and greater body dissatisfaction in relation to the male sex, tending to self-assess according to their bodily appearance. Key words: Adolescence, risky eating behaviors, self-perception, body dissatisfaction.